FUNGSI TEMONG-TEMONG DALAM ACARA BABAKO DI KELURAHAN BINUANG KAMPUNG DALAM KECAMATAN PAUH PADANG - Yut Nurrahmi; Marzam Marzam; Esy Maestro (SENDRATASIK UNP, 2013)
Abstract The research aimed at understanding the function of Temong-temong during babako. The method of the research was qualitative. The research showed that there were several functions of Temong-temong during babako. 1) symbolic function, with the music from Temong-temong during babako, it could rimove bad assumptions from the society toward those who wre menaging a wedding. 2) communication  function, with the music from Temong-temong people knew that there was a wedding. 3) entertainment function, with the music from Temong-temong the people could be entertained. 4) Revaling expression emotional function, for those who saw and heatd the music would join the celebration cheerfully.   Kata Kunci: Fungsi, Temong-temong, Babako, Kecamatan Pauh